Understanding Saudi’s preferences of emergency physicians attire a cross-sectional study - Alsalamah, Majid; Aldahaian, Dahian; Alghamdi, Khaled; Alharthi, Falwah; Albusair, Malek; Algharbi, Abdullah (International Journal of Research in Medical Sciences, 2023)
Background: Patient centered care (PCC) is defined as the practice of attending to patients that includes listening, informing, and involving patients in their health care as per picker’s eight principles. A part of the patients’ rights is the presentation of the caring physician which includes attitude and attire. In Saudi Arabia, it has been known that doctors present with white coat. Several studies showed that physician dress-code improve patients’ satisfaction. Our aim in this study is to identify Saudi population preference on the attire of emergency physicians. Methods: This was cross-sectional study in Riyadh, Saudi Arabia. Questions were asked to Saudi population in malls and hospital’s waiting areas regarding physician attire by online survey. Participants were asked demographic questions then they were asked in detail about their preferences. Results: Total 486 participated in the study, where 52.15% strongly care about emergency physician’s look. 82% would like to see their male physician wearing scrubs/medical coat, 43% agreed on a face cover for their female physician but still prefer scrubs/medical coat with 45%. Lastly participants had equal thoughts when it came to experience and reliability as 38% agree that looks can affect these two qualities. When it came to the relation of looks to knowledge as percentage were very close with 31% neutral and 32% agreed. Conclusions: Both Saudi sexes equally consider emergency physician external look as a representation on their respectfulness, reliability, and experience, but not that significant to the knowledge he has.